Implementasi Charger HP dengan Panel Surya - Suwarno Suwarno; Muhammad Fitra Zambak (Website, 2022)
Abstract This paper provides a solution for charging cell phones (HP) using solar panels. The need for electrical energy consumption is increasing, so renewable energy sources are needed that must meet the requirements, namely to produce energy that is environmentally friendly, at economical costs. The use of solar panels is a wise thing for current conditions as an alternative energy source to be used as a source of charging cell phones (mobile phones). The use of solar panels as a source of electrical energy to facilitate battery charging when outdoors or when there is no other power source. In this study, a solar panel of 10 Wp, 21V dc is used as a power source and a buck converter as a voltage reducer from 12V to charge a 6V, 4500 mAh battery. The number of cellphones that use this battery charger is 4, while observations when charging cellphones are in the form of battery percentage from 50% to 100% with a charging time of 1 hour 30 minutes. Makalah ini memberikan suatu solusi untuk mengisi batere Handphone (HP) menggunakan panel surya. Kebutuhan akan konsumsi energi listrik semakin meningkat, maka diperlukan sumber energi terbarukan yang harus memenuhi syarat untuk menghasilkan energi yang ramah lingkungan, biaya ekonomis. Penggunaan panel surya merupakan hal yang bijak untuk kondisi saat ini sebagai sumber energi alternative untuk dimanfaatkan sebagai sumber pengisian batere telepon seluler (handphone). Penggunaan panel surya sebagai sumber energi listrik untuk memudahkan pengisian batere saat berada di luar ruangan atau saat tidak ada sumber listrik lainnya. Pada penelitian ini menggunakan panel surya 10 Wp, 21V dc yang berfungsi sebagai sumber listrik dan buck converter sebagai penurun tegangan dari 12V untuk mengisi batere 6V, 4500 mAh. Jumlah handphone yang menggunakan sumber pengisi batere ini sebanyak 4, sedangkan pengamatan saat pengisian batere HP berupa persentasi batere dari 50% ke 100% dengan waktu pengisian 1 jam 30 menit.